2017
DOI: 10.5812/aapm.44132
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Minimum Data Set (MDS) for C-Section Anesthesia Information Management System (AIMS)

Abstract: BackgroundCaesarean section, also known as C-section, is a very common procedure in the world. Minimum data set (MDS) is defined as a set of data elements holding information regarding a series of target entities to provide a basis for planning, management, and performance evaluation. MDS has found a great use in health care information systems. Also, it can be considered as a basis for medical information management and has shown a great potential for contributing to the provision of high quality care and dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 27 publications
0
23
0
Order By: Relevance
“…To collect quality data and achieve integrated health information system, we need a minimum data set (16), because MDS is considered to be a primary step in the national information system (17). Hawes et al showed that, using a minimum set of data increases the accuracy and comprehensiveness of the medical information and ultimately leads to the provision of high quality health care (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To collect quality data and achieve integrated health information system, we need a minimum data set (16), because MDS is considered to be a primary step in the national information system (17). Hawes et al showed that, using a minimum set of data increases the accuracy and comprehensiveness of the medical information and ultimately leads to the provision of high quality health care (18).…”
Section: Discussionmentioning
confidence: 99%
“…Some of the data elements that were verified by experts in the present study have also been approved by the experts of other fields. For example, patient personal information, pre-treatment evaluations, drug therapies and therapeutic interventions were among the factors that had been considered as the minimum data required in cystic fibrosis information systems, athletic health records, orthopedic injuries, breast cancer, nursing and burns (18). This similarity suggests the need for these data sets in many care systems.…”
Section: Discussionmentioning
confidence: 99%
“…Using an MDS for surveillance reports as an effective tool for delivering high-quality care is essential. [24][25][26] The aim of MDSs is to determine data elements that should be considered for each patient and to provide consistent definitions of the necessary information for common terminology. 27 One of these standards is the International Classification of Diseases (ICD) system developed by WHO.…”
Section: Introductionmentioning
confidence: 99%
“…Development and implementation of an MDS is the first and most important step in collecting accurate, standardized, and comparable data at regional, national, and international levels, which can be applied to collect data in a specific scope. Using an MDS for surveillance reports as an effective tool for delivering high‐quality care is essential 24‐26 . The aim of MDSs is to determine data elements that should be considered for each patient and to provide consistent definitions of the necessary information for common terminology 27 …”
Section: Introductionmentioning
confidence: 99%
“…Providing a minimum dataset in a manual or computer-based system can be the basis for unifying and integrating documented data from different institutions and systems for easy data comparison. [ 21 22 ]…”
Section: Introductionmentioning
confidence: 99%